Coffee yield is influenced by soil properties, not by nitrogen fertilization strategies, under greenhouse gas monitoring in a Costa Rican Andisol - Giraldo-Sanclemente, Weynner; Pérez-Castillo, Ana Gabriela; Elizondo-Barquero, Marcelo; Rodríguez-Solís, Carlos Mario (Frontiers in Agronomy, 2025)
In recent years, Costa Rican coffee farms have increased nitrogen (N) inputs to maximize yields, using different rates, timings, and sources. N is often applied in complete fertilizers that include phosphorus (P), a limiting nutrient in Andisols due to their physical and chemical properties. However, excessive N use raises concerns about greenhouse gas (GHG) emissions and soil acidification. In 2024, a field trial was conducted for eight months at the Alsacia Coffee Farm (Starbucks Company) in Alajuela, Costa Rica, to evaluate coffee yield and quantify nitrous oxide (N2O) and methane (CH4) emissions under three N fertilization strategies, considering soil interactions. The experiment used 15 × 16 m plots in six randomized complete blocks across two sectors (A and B) with contrasting microtopography. Treatments included: urea (U; 414 kg N ha-¹, split into two applications), urea + urease inhibitor NBPT (F; 346 kg N ha-¹), and ammonium nitrate (Y; 346 kg N ha-¹), the last two split into three applications. No significant yield differences were observed during one crop cycle among treatments; however, yield was strongly affected by soil properties. Sector A, with 50% more clay and higher P, doubled the yield compared to Sector B. N2O cumulative emissions were similar for F and Y but higher in U due to greater N input. Soils acted as a CH4 sink. Although treatment F had lower yield-scaled emissions (74 ± 20 g CO2e kgcoffee-¹) than U (146 ± 47 g CO2e kgcoffee-¹), the environmental impact was limited. Results highlight the importance of site-specific nutrient and soil management to improve sustainability in coffee production. Under the experimental conditions, soil texture and phosphorus content were key factors influencing coffee productivity.